Aislamiento e Identificación de Microorganismos Fermentadores de una Bebida Ancestral fermentada (chicha) a partir de Chonta (bactris gasipaes h.b.k) - Murillo Gallardo, Erika Lisbeth (2019)
This research was developed at Technical University of Cotopaxi in microbiology laboratories of Agro industrial Engineering where were aimed the identification and isolation fermenting microorganisms of ancestral drink from chonta (chicha). (bactris gasipaes h.b.k) , the purpose of this research was to insolate and identify fermenting microorganisms to technify and give new alternatives to the community marking of process of making this drink. At isolation, through the seedtime technique was used on a suitable solid medium crop in a Petri plate. Each bacterial colony has certain characteristics in its shape, edge, elevation, size and consistency for insolation agar Saboraud dextrose were used, the technique of fluted in four quadrants and the colony purity was verified by simple staining with blue methylene, and Gram staining with violet crystal, lugol, alcohol and safranine, identification was done by API NE 50 CHL biochemical tests. 30 plates were isolated, 14 were lactic acids, 10 of leaven identifying and characterizing to3 lactic acids strains and two biochemically and morphologically leaven though biochemical tests, it was possible to identify lactic acid bacteria such as bacillus, lactobacillus, Sporolactobacillus, which are Gram positive for endospores and leaven such as Saccaromyces cerevisiaea, candida utilis